1958
DOI: 10.1002/bscb.19580671102
|View full text |Cite
|
Sign up to set email alerts
|

Sur le Comportement Anodique du Cuivre III. Etude de la Passivation

Abstract: It has been shown that anodic oxidation of copper in alkaline solutions leads to a true passivation due to the formation of a protective layer. The properties of this layer depend on various factors such as current density, structure of the metal, electrolyte concentration and temperature.In all cases investigated in this paper, the primary product of anodic oxidation was cuprous oxide. But this cuprous compound is rapidly oxidised to cupric oxide or hydroxide which are the main constituents of the final film.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1959
1959
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…The position at which the conduction band is pinned at the surface relative to the vacuum level is the electron affinity (EA) of the semiconductor. It can be related to solution measurements which are normally referenced to the standard calomel electrode (SCE), since this half-cell is at a fixed potential relative to the vacuum level (7). In electrochemistry the analogous quantity to electron affinity…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The position at which the conduction band is pinned at the surface relative to the vacuum level is the electron affinity (EA) of the semiconductor. It can be related to solution measurements which are normally referenced to the standard calomel electrode (SCE), since this half-cell is at a fixed potential relative to the vacuum level (7). In electrochemistry the analogous quantity to electron affinity…”
Section: Discussionmentioning
confidence: 99%
“…Equation [5] may be rewritten i(t) = 4ira(S) (1 --S) [6] where im is the maximum of the potentiostatic current-time transient and S is the surface coverage function (0 ~ S ~ 1). If it is assumed that im and tm are exponential functions of potential, then ir~ = (nFkJ4) : 10 a~'+~ [7] tm = (p2 9 in (2)/GM~k12No) : 10 a*'E+b2 [8] Equations [5]- [8] may be regarded as a set of differential equations specifying i as a function of t for various E in the case of three-dimensional instantaneous nucleation. The entire galvanostatic E (t) response can be calculated by numerical solution (see below) or exact solutions can be calculated for certain limiting cases.…”
Section: Polycrystalline Copper Electrodes--cyclicmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Bouillon et al found that only CuO was observed at low current density (< 0.5 mA cm -2 ), and Cu(OH)2 was dominant at above 0.8 mA cm -2 . 29 In the light of these previous reports, we can interpret our results as followings: 1) at 0.1 mA cm -2 , Cu foil is covered with only the porous Cu2O particles because of a small current density for the growth of Cu(OH)2 or CuO films; 2) sheet-shape CuO mainly grows at 0.5 mA cm -2 ; 3) the growth of 1D Cu(OH)2 nanostructures, competing with the formation of CuO, become more favorable with increasing a higher current density between 1 -2 mA cm -2 . Gas bubbles were evolved from the surface of the copper foil in the electrochemical anodization above 5 mA cm -2 .…”
Section: The Concentration Of Nucleophile Ohmentioning
confidence: 99%
“…The anodic corrosion of copper electrodes in hydroxide solutions has been variously investigated (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), particularly by means of galvanostatic charging curves, following Hickling and Taylor (3). Generally, two clear steps were found in the traces before oxygen was evolved, and, from the results of subsequent examinations and/or by reasonable correspondence of the measured potentials to calculated thermodynamic values, these were assigned to the electrode reactions Cu/Cu20 and Cu/Cu (OH)2 (and/or Cu/CuO).…”
mentioning
confidence: 99%